PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IIC SD NEGERI 8 PEKANBARU - Novriani '; Zulkifli '; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The research carried out base on the lowly of the result of mathematic in grade IIC SD Negeri 8 Pekanbaru which is about 59,4 from 27 students within minimal completeness criterion (KKM) stated is 70. This research is classroom action research (CAR). The purpose of this research is to improve mathematic learning process of class IIC SD Negeri 8 Pekanbaru in academic year 2014/2015 through cooperative learning type Talking Stick. The research was conducted into 2 cycles. Each cycle consist of two meeting and one test. The instrument used in this study is the teacher and student’s activity sheet as well as learning about the test result. This study presents an increase of average teacher’s activity in the first cycle in first meeting is 71%, the second meeting increase to 79%. The second cycle increase from 88% to 96%. Student activity based on the result of research on first cycle is from 67% in the first meeting to 75% in the second meeting. In the second cycle increase from 83% in the first meeting to 92% in the second meeting. Based on the research of students learning outcome increased from the base score 59,4 to 79,8 in the first cycle and the second cycle increase become 93,8. Based on the result of the research, it can be concluded that the implementation of cooperative learning type Talking Stick can improve the student’s achievement in mathematic subject of class VA SD Negeri 8 Pekanbaru.Key words: Talking Stick, Cooperative Learning, Student’s Mathematic Achievement.